EGb 761 reduces Ca2+ influx and apoptosis after pentylenetetrazole treatment in a neuroblastoma cell line - Ovey, Ishak Suat; Ozsimsek, Ahmet; Velioglu, Halil Aziz; Altay, Ozlem; Mardinoglu, Adil; Yulug, Burak (Frontiers in Cellular Neuroscience, 2023)
Background: Transient receptor potential (TRP) channels have been found to have significant implications in neuronal outgrowth, survival, inflammatory neurogenic pain, and various epileptogenic processes. Moreover, there is a growing body of evidence indicating that transient receptor potential (TRP) channels have a significant impact on epilepsy and its drug-resistant subtypes.Objective: We postulated that EGb 761 would modulate TRPA1 channels, thereby exhibiting anti-inflammatory and neuroprotective effects in a neuroblastoma cell line.Our rationale was to investigate the impact of EGb 761 in a controlled model of pentylenetetrazole-induced generalized epilepsy.We evaluated the neuroprotective, antioxidant and anti-apoptotic effects of EGb 761 both before and after the pentylenetetrazole application in a neuroblastoma cell line. Specifically, we focused on the effects of EGB 761 on the activity of Transient receptor potential (TRP) channels.Results: EGb 761applications both before and after the pentylenetetrazole incubation period reduced Ca release and restored apoptosis, ROS changes, mitochondrial depolarization and caspase levels, suggesting a prominent prophylactic and therapeutic effect of EGb 761in the pentylenetetrazole-induced epileptogenesis process.: Our basic mechanistic framework for elucidating the pathophysiological significance of fundamental ion mechanisms in a pentylenetetrazole treated neuroblastoma cell line provided compelling evidence for the favorable efficacy and safety profile of Egb 761 in human-relevant in-vitro model of epilepsy. To the best of our knowledge, this is the first study to investigate the combined effects of EGb 761 and pentylenetetrazole on TRP channels and measure their activation level in a relevant model of human epileptic diseases.